No More Political Compromise? Swedish Commissions of Inquiry 1990–2016. (7th June 2021) - Dahlström, Carl; Lundberg, Erik; Pronin, Kira
Abstract : This article studies recent trends in the composition and uses of Swedish commissions of inquiry in preparing policy for the government. For much of the 20th century, commissions with representatives of major parliamentary parties and other policy stakeholders served as an arena of negotiation and compromise between the government, the opposition parties, and organised interests. Drawing on a unique data set of 2, 087 commissions appointed between 1990 and 2016, we show that their representativeness has declined significantly. We also document a significant decrease in the inclusion of politicians and an increase in the presence of civil servants. Governments have also increased their control over commissions by issuing more directives. We further document a dramatic decline of reservations and dissenting opinions in the commission reports. This may be due to a combination of including fewer potentially dissenting voices and restricting commissions' scope. We conclude that commissions are no longer the arenas of compromise‐seeking that they were for most of the 20th century.